5x+6x-3x-5=51

Simple and best practice solution for 5x+6x-3x-5=51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6x-3x-5=51 equation:


Simplifying
5x + 6x + -3x + -5 = 51

Reorder the terms:
-5 + 5x + 6x + -3x = 51

Combine like terms: 5x + 6x = 11x
-5 + 11x + -3x = 51

Combine like terms: 11x + -3x = 8x
-5 + 8x = 51

Solving
-5 + 8x = 51

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 8x = 51 + 5

Combine like terms: -5 + 5 = 0
0 + 8x = 51 + 5
8x = 51 + 5

Combine like terms: 51 + 5 = 56
8x = 56

Divide each side by '8'.
x = 7

Simplifying
x = 7

See similar equations:

| (4x^3+4x^2-3x)(x^2-7)=0 | | 5+(3x-3)=3x-(8x-6) | | C-50=28 | | 23=u-10 | | x(3x+2)=8 | | 30x^2-1=5x^2-1 | | x4=1/10 | | 6/7s-5/6s=4/21 | | 15=c/5 | | M+7m+3m-6= | | 2cos^2(2x)-cos(x)=0 | | 2s^2+3s-1=0 | | x^4-y^4-3y^2+1=0 | | -16x^2+75x-51=0 | | -6z=15-7z | | 2cos^2(2x)-cos(2)=0 | | 2x-3(x+3)=23 | | 4k-8=5(k+7) | | 25,200/525 | | x+18-9x=27-6x-9 | | 27=w-35 | | 1x+18-9x=27-6x-9 | | .007x=21 | | J+66=99 | | 66=f-6 | | 6=f/13 | | 4/5a=1/25 | | 4-2(x+4)+1=1 | | X/40*100=5 | | A/19=3 | | -3+2(x+9)=14x | | 15f=90 |

Equations solver categories